NGMSElect™ and Investigator® Argus X-12 analysis in population samples from Albania, Iraq, Lithuania, Slovenia, and Turkey. (May 2016) - Poulsen, L.; Tomas, C.; Drobnič, K.; Ivanova, V.; Mogensen, H.S.; Kondili, A.; Miniati, P.; Bunokiene, D.; Jankauskiene, J.; Pereira, V.; Morling, N.
Highlights: Five populations from Albania, Iraq, Lithuania, Slovenia, and Turkey were investigated. Two sets of forensic genetic markers were used: NGM SElect™ (646 individuals), and Argus X-12 (534 individuals). No statistically significant deviations from HWE were observed and pairwise LD was only detected in X-STRs between markers located in the same linkage group. Comparison with published data showed that the populations in this study had lower pairwise FST values with those populations that are geographically close. The power of discrimination values for males and females and the probability of exclusion in duos and trios were high for the populations in this study. Abstract: The analysis of STRs is the main tool when studying genetic diversity in populations or when addressing individual identification in forensic casework. Population data are needed to establish reference databases that can be used in the forensic context. To that end, this work investigated five population samples from Albania, Iraq, Lithuania, Slovenia, and Turkey. Individuals were typed for 16 autosomal STRs and 12 X-chromosomal STRs using the NGMSElect™ and Investigator ® Argus X-12 kits, respectively. The aim of the study was to characterize the diversity of both STR kits in these population samples and to expand our forensic database. The results showed that all markers were polymorphic in the five populations studied. No haplotype was shared between the males analysed for X-STRs. No statistically significant deviations from Hardy–Weinberg equilibrium were observed for any of the genetic markers included in both the kits. Pairwise LD was only detected in X-STRs between markers located in the same linkage group. Power of discrimination values for males and females and the probability of exclusion in duos and trios were high for the populations in this study.